2014
DOI: 10.1371/journal.pone.0095674
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Reduces Avian Reproductive Success and Imposes Selection: An Experimental Study with Adult- or Lifetime-Exposure in Zebra Finch

Abstract: Mercury is a global pollutant that biomagnifies in food webs, placing wildlife at risk of reduced reproductive fitness and survival. Songbirds are the most diverse branch of the avian evolutionary tree; many are suffering persistent and serious population declines and we know that songbirds are frequently exposed to mercury pollution. Our objective was to determine the effects of environmentally relevant doses of mercury on reproductive success of songbirds exposed throughout their lives or only as adults. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 50 publications
1
64
3
Order By: Relevance
“…Baker et al (1985) reported that in the marine gastropod, Cerithium rupestre, Hg resistance is reinforced at Hg polluted sites, presumably by natural selection for increased resistance and that Hg resistance in their study was associated with sites of high Hg pollution. Selection for resistance to mercury has also been demonstrated in birds chronically exposed to high levels of mercury over their lifetime (Varian-Ramos et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Baker et al (1985) reported that in the marine gastropod, Cerithium rupestre, Hg resistance is reinforced at Hg polluted sites, presumably by natural selection for increased resistance and that Hg resistance in their study was associated with sites of high Hg pollution. Selection for resistance to mercury has also been demonstrated in birds chronically exposed to high levels of mercury over their lifetime (Varian-Ramos et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In birds and mammals, mercury adversely affects reproduction, growth and development, nervous system, and metabolism (Varian-Ramos et al, 2014, Dietz et al, 2012. In addition, mercury in aquatic organisms can also disrupt blood chemistry the ability for osmoregulation, and oxygen exchange.…”
Section: Environmental Effects Of Mercurymentioning
confidence: 99%
“…In addition, organomercury is acutely toxic to aquatic microorganisms and invertebrates. Organic mercury compounds 10 -100 times more toxic than the inorganic forms making bioaccumulated mercury a significant risk to aquatic organisms and organisms that consume them (Varian-Ramos et al, 2014).…”
Section: Environmental Effects Of Mercurymentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have documented the effects of mercury (Hg) on the health and fitness of aquatic bird species, but studies focusing on terrestrially foraging birds are fewer (Seewagen 2010). Recent research suggests that songbirds can suffer reduced reproductive success Hallinger and Cristol 2011;Varian-Ramos et al 2014), altered stress hormone profiles (Franceschini et al 2009;Wada et al 2009), and disrupted immune functioning (Hawley et al 2009;Lewis et al 2013) in response to Hg exposure, but more research is needed to fully understand the potential impact of MeHg on the health and fitness of terrestrially foraging species.…”
Section: Introductionmentioning
confidence: 99%